1997
DOI: 10.1001/jama.1997.03540300040031
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber, Glycemic Load, and Risk of Non—insulin-dependent Diabetes Mellitus in Women

Abstract: Our results support the hypothesis that diets with a high glycemic load and a low cereal fiber content increase risk of diabetes in women. Further, they suggest that grains should be consumed in a minimally refined form to reduce the incidence of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
756
5
25

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,425 publications
(816 citation statements)
references
References 67 publications
30
756
5
25
Order By: Relevance
“…In the general population, these risk factors can be effectively lowered through interventions focusing on changes in nutrition and physical activity. [149][150][151] With a suggested increased risk of noncommunicable diseases within populations with ID, special attention needs to be paid to the efficacy and effectiveness of multicomponent behaviour change interventions to reduce this disparity. However, there is a lack of quality evidence on the health and health care of people with ID, including the effectiveness of health interventions.…”
Section: Rationalementioning
confidence: 99%
“…In the general population, these risk factors can be effectively lowered through interventions focusing on changes in nutrition and physical activity. [149][150][151] With a suggested increased risk of noncommunicable diseases within populations with ID, special attention needs to be paid to the efficacy and effectiveness of multicomponent behaviour change interventions to reduce this disparity. However, there is a lack of quality evidence on the health and health care of people with ID, including the effectiveness of health interventions.…”
Section: Rationalementioning
confidence: 99%
“…The inconsistencies may result from difficulties in measuring the glycemic potential of diet, given the importance of meal composition, for example. However, glycemic load measured from FFQs has strongly predicted the risk of coronary heart disease (Liu et al, 2000) and type II diabetes (Salmeron et al, 1997). Glycemic load may increase the risk particularly among susceptible subgroups; one study observed increased risk of breast cancer only among those with elevated BMI (Cho et al, 2003a).…”
Section: Carbohydratesmentioning
confidence: 99%
“…These lifestyle and behavior patterns modifications include obesity (COLDITZ et al, 1990;, low physical activity (HELMRICH et al, 1991;HU et al, 1999;LYNCH et al, 1996;MANSON et al, 1991), smoking addiction (MANSON et al, 2000;RIMM et al, 1995), low fiber diet with a high Glycemic Index (DIABETES…, 1993b;INSTITUTE…, 2000;U. K. PROSPECTIVE…, 1998) In this study, we refer to obesity as the body mass index higher than 25 (SALMERON et al, 1997). Doing sport is defined as activities done twice a day with the duration of at least 30 minutes including jogging which causes rapid breathing (LIU et al, 2000b;SALMERON et al, 1977).…”
Section: Resultsmentioning
confidence: 99%